Covalent sidewall functionalization of SWNTs by nucleophilic addition of lithium amides - Syrgiannis, Zois; Hauke, Frank; Röhrl, Jonas; Hundhausen, Martin; Graupner, Ralf; Elemes, Yiannis; Hirsch, Andreas (European Journal of Organic Chemistry, 2008)
The synthesis and characterization of sidewall-functionalized SWNT derivatives (nPrNH)-SWNTs containing n-propylamine addends is reported. The nucleophilic addition of in situ generated lithium n-propylamide to the sidewall of SWNTs and the subsequent reoxidation of charged intermediates of the type (nPrNH)-SWNT- leads to carbon nanotube derivatives with covalently attached amino groups. Based on the reaction sequence, a homogeneous dispersion of the carbon nanotube material is achieved as a result of the electrostatic repulsion of negatively charged intermediates. The solubility of the resulting propylamine-functionalized (nPrNH) -SWNT material in organic solvents is drastically increased. The functionalized tubes were characterized in detail by Raman spectroscopy, thermogravimetric analysis (TGA/MS), X-ray photoelectron spectroscopy (XPS) and UV/Vis/NIR spectroscopy. © Wiley-VCH Verlag GmbH & Co. KGaA, 2008.